Neuro - Puzzy Analysis for Silicon Carbide:Abrasive Grains Production (2010)
The paper presents a control system for grinding process using fuzzy rule-based model for estimating the grinding conditions at which wheel wears occur. The grinding parameters include circumferential speed or a grinding segment workpiece velocity and work depth of cut using silicon carbide grinding wheels. There was a wide range of applications over many types of mild steel materials and various wheel wear values were recorded for predicting the grinding conditions. Grinding wheels with various wheel hardness grades ranging from soft (H grade) to hard (R grade) and wide range of grit sizes, ranging from coarse to fine.